Aligning policy ideas and power: the roots of the competitiveness frame in European education policy. Issue 4 (1st October 2020) - Cino Pagliarello, Marina
ABSTRACT: How and why do some ideas attain agenda status while others do not? This paper seeks to explore these questions in the context of the policy changes observed in European education policy. By drawing from the literature on agenda-setting and employing process tracing, the paper develops a theoretical argument to investigate the causal mechanisms through which a new problem definition is set. The central argument is that three factors affect how a problem definition wins over another: (i) the presence of a policy entrepreneur; (ii) the ability to construct a convincing narrative to support a particular interpretation of a problem; and (iii) the specific zeitgeist of a given period, namely the social and political context within which ideas gain ground. The paper contributes to the literature on European education policy by examining how ideas about education emerged. It also contributes to the theoretical debate on agenda setting studies.